Decision Support System for Selecting the Best Head of Study Program Applying the Multi-Objective Optimization Method on the Basis of Simple Ratio Analysis (MOOSRA) - Lubis, Juanda Hakim; Sanwani, Sanwani; Lubis, Akhyar; Mesran, Mesran; Julaysa, Julaysa; Hutapea, Novita Sari (Bulletin of Informatics and Data Science, 2025)
The Head of Study Program plays an important role as the highest leader in the structure of a study program. The Head of Study Program is responsible for the smooth running of academic activities in the study program he leads. As a key element in higher education, the Head of Study Program must lead the managerial function by planning, implementing, and controlling the academic process and managing other supporting activities. The head of the study program who shows high performance, dedication, and integrity deserves an award as the best head of the study program. This assessment aims to ensure that the Head of Study Program is able to carry out his duties properly in accordance with the rules and demands, and advance the study program in accordance with its vision and mission. Therefore, a decision support system is needed as a solution to overcome this problem, by utilizing the MOOSRA method. MOOSRA begins by formulating a decision matrix consisting of alternatives, criteria or attributes, individual weights or significance coefficients of each criterion, and performance measurements of related alternatives. Normalization is then carried out to change the attribute values into the range 0–1. The assessment results show that the Head of Study Program with the highest ranking is alternative A7, with a value of 0.896358